Caracterização das solicitações de atendimento populacional relacionadas às doenças cardiovasculares ao Serviço de Atendimento Móvel de Urgência (SAMU) de uma cidade do interior paulista: coorte retrospectiva - Costa, Nadia Maria Santos (Universidade Federal de São Carlos, 2022)
Objective: To characterize the requests for population care related to cardiovascular diseases to the Mobile Emergency Care Service of a city in the interior of São Paulo. Method: Retrospective study, developed at the Medical Regulation Center of the Mobile Emergency Service of a municipality located in the interior of São Paulo in the southeastern region of the country. Results: In the months of January to June 2021, 329 (100%) requests for assistance were made for Cardiovascular Diseases, the largest number of requests for assistance corresponds to Unstable Angina and Acute Myocardial Infarction, with 105 (31.9%) of the total of attendances, about 74 (22.5%) correspond to requests classified as hypertensive crisis. When the age group is stratified, requests for female patients predominate, with an occurrence greater than or equal to male patients in all months, except in the month of April in the age group between 41-50 years, regarding the care for Acute Coronary Syndrome male patients prevailed in greater numbers in January, February, March, May and June, regardless of the age group analyzed. Conclusion: The study characterized the requests for population care related to cardiovascular diseases to the Mobile Emergency Care Service of a city in the interior of São Paulo. Male sex is associated with higher rates of occurrence of Cardiovascular Diseases and the highest rates of requests occurred due to Hypertensive Crisis and Systemic Arterial Hypertension together with Acute Coronary Syndrome. In this sense, the characterization of requests from the mobile emergency care service can collaborate with the prevention work with the population as well as the monitoring of reference services.
Characterization of the population's requests for care related to cardiovascular diseases to the Mobile Emergency Care Service (SAMU) of a city in the interior of São Paulo: retrospective cohort
Keywords: Ambulância; Urgência; Emergência; Ambulance; Urgency; Emergency; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM MEDICO-CIRURGICA